Examining The Role of Bank Interest Haram Fatwa on Factors Influencing Customer Desires - Mochlasin, Mochlasin (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research tries to explain the actual use of customers in the context of sharia banking in DIY. Specifically, this research aims to examine the role of fatwa knowledge in moderating the relationship between customer satisfaction, customer trust, and religious motives with behavioral intentions. A survey was conducted to collect data, resulting in 300 complete usable responses. Moderated Regression Analysis (MRA) was used to test the research hypothesis. The findings of this research reveal that customer trust and religious motives influence behavioral intentions, while customer satisfaction and fatwa knowledge have no influence. However, knowledge about the fatwa issued by the MUI was found to mediate the influence of customer satisfaction on behavioral intentions but did not mediate customer trust and religious motives on behavioral intentions. Additionally, behavioral intentions were found to influence actual usage by customers. Ultimately, this research provides valuable insights for practitioners and policy makers in the sharia banking industry to create actual utilization and increase customer literacy regarding fatwas in sharia banking.